2016
DOI: 10.5194/angeo-34-75-2016
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the big storm events in the first half of 2015 on the radiation belts observed by EPT/PROBA-V

Abstract: Abstract. With the energetic particle telescope (EPT) performing with direct electron and proton discrimination on board the ESA satellite PROBA-V, we analyze the highresolution measurements of the charged particle radiation environment at an altitude of 820 km for the year 2015. On 17 March 2015, a big geomagnetic storm event injected unusual fluxes up to low radial distances in the radiation belts. EPT electron measurements show a deep dropout at L>4 starting during the main phase of the storm, associated to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 32 publications
4
28
0
Order By: Relevance
“…The peak ozone anomaly occurs in August around 3 hPa, reaching ∼ 15 %. Our results agree with the results from previous modelling studies (Reddmann et al, 2010;Rozanov et al, 2012;Sinnhuber et al, 2018) and observations (Damiani et al, 2016;Fytterer et al, 2015).…”
Section: O 3 Anomaly Propagationsupporting
confidence: 93%
“…The peak ozone anomaly occurs in August around 3 hPa, reaching ∼ 15 %. Our results agree with the results from previous modelling studies (Reddmann et al, 2010;Rozanov et al, 2012;Sinnhuber et al, 2018) and observations (Damiani et al, 2016;Fytterer et al, 2015).…”
Section: O 3 Anomaly Propagationsupporting
confidence: 93%
“…While a further dedicated investigation should be undertaken, many of the shock-sheath structures discussed here have been studied recently for their strong effects on radiation belt electrons (for example, 1 and 8 October 2012 [Baker et al, 2013;Turner et al, 2014]; Hudson et al, 2014], 17 March 2013 [Boyd et al, 2014], 12 September 2014 [Alves et al, 2016], 17 March 2015 [Pierrard and Lopez Rosson, 2016;Li et al, 2016], and 22-25 June 2015 [Baker et al, 2016]). We have found that one of the conditions that makes shock-sheath structures geoeffective is a relatively steady southward B z upstream of the shock due to a preceding transient or preexisting southward IMF in the solar wind.…”
Section: Discussionmentioning
confidence: 99%
“…Such storms are characterized first by a dropout during the main phase, generally followed by a flux increase in the outer belt and injections in the slot region. Some injections even reach the inner belt during several storms, mainly during the more severe ones appearing in 2015 (Pierrard & Lopez Rosson, ) but also in 2016 and 2017.…”
Section: Time Variations In Ept Observationsmentioning
confidence: 99%